Deriving Public Innovation Capacity: Evidence From the Korean Public Sector - Min Young Kim; Sang Woo Kim (Frontiers in Psychology, 2022)
By actively coping with changes, a government providing public services can also improve the quality of those public services and help citizens improve their quality of life in the face of rapidly changing social structures, environments, and values. Accordingly, this study will typologize public innovation capacity (PIC) in terms of the individual, middle manager, and organizational levels. This study typologizes public innovation capacity in terms of the individual, middle manager, and organizational levels through mini-round Delphi analysis and exploratory factor analysis and confirmatory factor analysis using survey. This capacity is a precondition of the specificity of the public sector (generating public interest by providing public services) and universal value of HR (human resource) research (creating performance). It provides the basic capacity within the public sector to enhance the quality of public services and create positive outcomes.